LEGAL INSTITUTIONALIZATION OF PUBLIC GOVERNANCE WITHIN RECENT SOCIAL TRANSFORMATIONS - T. V. Kovalova (Pressing Problems of Public Administration, 2022)
The article substantiates the expediency of applying the neoinstitutional approach to the study of legal institutionalization processes under the conditions of social changes, defines the role of legal institutionalization in public governance considering some factors promoting or, on the contrary, hinder effectiveness of legal institutions. The neo-institutional approach is a relevant methodological basis for the study of the development of the legal system under the conditions of social transformations and reforming of state administration. In the concept of formal institutionalization, legal institutionalization means the formation of new legal institutions, the formalization of certain social relations and social ties. However, revealing the essence of legal institutionalization from the formal side is far from the only approach related to the perception of institutionalization as a law-making phenomenon. In opposition to the concept of formalization, ideas about the decisive role of the substantive component in the institutional process are put forward. According to this theory, the creation of legal institutions does not depend on their formal recognition by the legislator. This actually means that legal institutions are formed and developed in parallel with regulative legal acts, but the form of law is not perceived as an indicator of the existence of one or another institution. The basis of institutionalization is the legal relation itself which is combined into certain types based on systemic features In connection to the expansion of the essence of legal regulation, the purpose of legal institutionalization has changed. As a result, it is possible to explain the emergence of numerous institutions which do not have any formal legal consolidation. In order to understand the nature and logic of the development of institutions, it is necessary to study the factors that guide society, citizens, and social groups in their actions, that is, to study institutions. The success of institutionalization mainly depends on national specifics and the state of socio-economic development of the country. The article has a theoretical-methodological character, and the material presented in it can be the basis for the study of legal institutionalization in various spheres of public administration.